Determinan DETERMINAN PENGARUH AUDITOR TERHADAP KUALITAS AUDIT (Studi Empiris pada Auditor di Kantor Akuntan Publik Propinsi Daerah Istimewa Yogyakarta): (Studi Empiris pada Auditor di Kantor Akuntan Publik Propinsi Daerah Istimewa Yogyakarta) - Isfaatun, Eliya; Istanto, Luluk Isnaini; Supardi, Supardi (PRIMA EKONOMIKA, 2024)
ABSTRACT Development of the auditor profession has a major impact on the development of the accounting profession. Audit quality is an important issue for various parties with an interest in financial statements. Research with the aim of examining and analyzing the effect of partially auditor competence, auditor skepticism and auditor independence on audit quality in auditors working in the Public Accounting Firm of the Special Province of Yogyakarta. The population in this study is 350 auditors who work in 8 (eight) public accounting firms in the Special Region of Yogyakarta. Determination of the number of samples using the Slovin formula with a result of 80 auditors. The analytical method uses the Multiple Linear Regression approach. The results of the study prove that auditor competence, auditor skepticism and auditor independence have a positive and partially significant effect on audit quality. The higher the level of Auditor Skepticism and the higher the level of Auditor Independence, the higher the level of Audit Quality in the 8 (eight) Public Accounting Firms in the Province of the Special Region of Yogyakarta. . Keywords: Auditor Competence, Auditor Skepticism, Auditor Independence, Audit Quality, Public Accounting Firm